2021
DOI: 10.1002/1878-0261.13038
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of precision diagnostic testing for precision medicine approaches against non‐small‐cell lung cancer: A systematic review

Abstract: Precision diagnostic testing (PDT) employs appropriate biomarkers to identify cancer patients that may optimally respond to precision medicine (PM) approaches, such as treatments with targeted agents and immuno‐oncology drugs. To date, there are no published systematic appraisals evaluating the cost‐effectiveness of PDT in non‐small‐cell lung cancer (NSCLC). To address this gap, we conducted Preferred Reporting Items for Systematic Reviews and Meta‐Analyses searches for the years 2009–2019. Consolidated Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Our recent health economic analyses have underlined the potential for cancer biomarkers to deliver value for money. [24][25][26] However, we also found a paucity of studies employing detailed health economic analysis to inform the feasibility of incorporating cancer biomarkers/genomic testing into the clinic, highlighting the need for wider deployment of health economic evaluation to inform value-based care. Precision diagnostics can also help target interventions to the most significant areas of disease.…”
Section: Cancer Research Domains Of Particular Strength In Europe: So...mentioning
confidence: 99%
“…Our recent health economic analyses have underlined the potential for cancer biomarkers to deliver value for money. [24][25][26] However, we also found a paucity of studies employing detailed health economic analysis to inform the feasibility of incorporating cancer biomarkers/genomic testing into the clinic, highlighting the need for wider deployment of health economic evaluation to inform value-based care. Precision diagnostics can also help target interventions to the most significant areas of disease.…”
Section: Cancer Research Domains Of Particular Strength In Europe: So...mentioning
confidence: 99%
“…In seeking to reduce R&D costs through earlier patient stratification by a CDx approach, pharmaceutical companies can better manage their oncology pipelines, improve timing of phase transitions into, ultimately, marketing authorizations for CDx-oncology medicines that deliver clinically meaningful benefit, in what is becoming a complex regulatory and competitive environment. Precision medicine has been hailed as a potential breakthrough for cancer patients and a disruptive technology which will potentially lower healthcare costs [ 3 , 5 ], but studies that deploy health economic analysis to determine the value of a precision medicine approach have been scarce [ 6 , 7 ]. Reducing R&D cost is not just beneficial for industry, but also provides a better environment for fair pricing and reimbursement on a country-by-country basis.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In the 2020 American Cancer Society Cancer Action Network survey, 29% of patients who discussed treatment plans with their providers decided to forgo biomarker testing because of its cost. 21 Finally, although biomarker testing for cancer targeted therapy for metastatic colorectal cancer and metastatic non-small cell lung cancer is mostly cost-effective, 22,23 a recent study showed that use of upfront NGS testing in patients with metastatic non-small cell lung cancer was associated with substantial cost savings and shorter time-to-test results in comparison with sequential testing of single analytes for both the Centers for Medicare & Medicaid Services (CMS) and commercial payers. 24 Studies show that currently only half of patients with cancer in the United States for whom biomarker testing is recommended are receiving the tests.…”
Section: Introductionmentioning
confidence: 99%